PENGARUH ASET PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PERUSAHAAN BADAN USAHA MILIK NEGARA (BUMN) TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TRIWULAN 2023-2024 - Rima Sundari; Luthfiyah Nabila Bela Satirah (LAND JOURNAL, 2026)
In the globalization era marked by information openness, companies are expected to provide financial statements that are both transparent and accountable. Nevertheless, pressures from diverse stakeholders often drive management to practice earnings management in order to enhance their financial appearance. The purpose of this research is to analyze the effect of deferred tax assets on earnings management in state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 quarterly period. This study applies a quantitative approach with secondary data obtained from annual reports. A total of four companies were chosen through purposive sampling. The analytical methods employed include product-moment correlation, simple linear regression, t-test, and coefficient of determination (R²), with data processing conducted using IBM SPSS Statistics 27. The findings reveal that deferred tax assets among the companies exhibit yearly fluctuations. In addition, the average earnings management score falls within the low to moderate range, suggesting that the firms do not engage in earnings management aggressively.